Pruritus in Systemic Diseases: A Review of Etiological Factors and New Treatment Modalities - Nagihan Tarikci; Emek Kocatürk; Şule Güngör; Ilteriş Oğuz Topal; Pelin Ülkümen Can; Ralfi Singer (The Scientific World Journal)
Pruritus is the most frequently described symptom in dermatology and can significantly impair the patient’s quality of life. In 10–50% of adults with persistent pruritus, it can be an important dermatologic clue for the presence of a significant underlying systemic disease such as renal insufficiency, cholestasis, hematologic disorder, or malignancy (Etter and Myers, 2002; Zirwas and Seraly, 2001). This review describes the presence of pruritus in different systemic diseases. It is quite important to discover the cause of pruritus for providing relief for the patients experiencing substantial morbidity caused by this condition.